[tex]\bf \textit{distance between 2 points}\\ \quad \\
\begin{array}{lllll}
&x_1&y_1&x_2&y_2\\
% (a,b)
&({{ -3}}\quad ,&{{ 2}})\quad
% (c,d)
&({{ m}}\quad ,&{{ 2}})
\end{array}\qquad
% distance value
d = \sqrt{({{ x_2}}-{{ x_1}})^2 + ({{ y_2}}-{{ y_1}})^2}[/tex]
[tex]\bf \textit{we know the distance from m,2 and -3,2(center) is the radius}
\\\\\\
d=8\implies 8=\sqrt{[m-(-3)]^2+[2-2]^2}
\\\\\\
8=\sqrt{(m+3)^2+(0)^2}\implies 8=\sqrt{(m+3)^2}\implies 8^2=(m+3)^2
\\\\\\
64=(m+3)^2\implies \sqrt{64}=\sqrt{(m+3)^2}\implies 8=m+3
\\\\\\
8-3=m[/tex]